Crop rotation with Meloidogyne-resistant germplasm is useful to manage and revert the (a)virulent populations of Mi1.2 gene and reduce yield losses - Fullana, Aïda Magdalena; Expósito, Alejandro; Escudero, Nuria; Cunquero, Marina; Loza-Alvarez, Pablo; Giné, Ariadna; Sorribas, F. Javier (Frontiers in Plant Science, 2023)
A rotation sequence of ungrafted and grafted tomato-melon-pepper-watermelon on resistant rootstocks ‘Brigeor’, Cucumis metuliferus, ‘Oscos’ and Citrullus amarus, respectively, was carried out in a plastic greenhouse, ending with a susceptible or resistant tomato crop. The rotation was conducted in plots infested by an avirulent (Avi) or a partially virulent (Vi) Meloidogyne incognita population to the Mi1.2 gene. At the beginning of the study, the reproduction index (RI, relative reproduction in the resistant respect susceptible tomato) of Avi and Vi populations was 1.3% and 21.6%, respectively. Soil nematode density at transplanting (Pi) and at the end (Pf) of each crop, disease severity and crop yield were determined. Moreover, the putative virulence selection and fitness cost were determined at the end of each crop in pot tests. In addition, a histopathological study was carried out 15 days after nematode inoculation in pot test. The volume and number of nuclei per giant cell (GC) and the number of GC, their volume and the number of nuclei per feeding site in susceptible watermelon and pepper were compared with C. amarus and resistant pepper. At the beginning of the study, the Pi of Avi and Vi plots did not differ between susceptible and resistant germplasm. At the end of the rotation, the Pf of Avi was 1.2 the Pi in susceptible and 0.06 in resistant, the cumulative yield of grafted crops was 1.82 times higher than that of the ungrafted susceptible ones, and the RI in resistant tomato less than 10% irrespective of the rotation sequence. Concerning the Vi, Pf was below the detection level at the end of the rotation in resistant and 3 times Pi in the susceptible. The cumulative yield of grafted crops was 2.83 times higher than that of the ungrafted and the RI in resistant tomato was 7.6%, losing the population’s virulence. In the histopathological study, no differences in number of GC per feeding site were observed in watermelon compared to C. amarus, but they were more voluminous and contained higher number of nuclei per GC and per feeding site. Regarding pepper, Avi population did not penetrate resistant rootstock.